THE EFFECT OF SUBSTITUTION OF WHEAT FLOUR TO SEAWEED FLOUR (Eucheuma cottonii) ON THE QUALITY OF PIE CUP DURING COLD STORAGE (50C) - Laura Armanda; Syahrul Syahrul; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aimed to determine the effect of substitution of wheat flour to seaweed flour (Eucheuma cottonii) with various concentrations on the quality of pie cup during cold storage.The research method used was a non factorial randomized block design (RBD) with 6 levels, namely: seaweed flour F0 (0%), F20 (20%), F40 (40%), F60 (60%), F80 (80%), and F100 (100%).Meanwhile, as a block was the storage time, namely 0, 7, 14, and 21 days.The results showed that the substitution of seaweed flour 20% (F20) gave the best results with the characteristics of intact appearance, neat, bright brown color (8.0), specific aroma of pie cup (6.9), savory taste (7.8),and crunchy texture (7.8) with a moisture content value of 1.84%, fiber content 0.12%, and a total plate number of 2.95 x 103 cfu/g for 14 days of storage.Keywords: Seaweed, Flour, Pie skin